Perancangan Dashboard Performansi di Bidang Kemahasiswaan dan Lulusan - Murtiastuti, Noviana Dwi; Liquiddanu, Eko; Priyandari, Yusuf (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2023)
Higher education institutions often face a number of challenges in managing data and reporting information effectively, such as limited availability and distribution of information. This also happened in the Industrial Engineering Study Program at Sebelas Maret University (PSTI UNS). PSTI UNS needs a performance monitoring platform for study programs in the field of student and graduate affairs to support study program management and quality assurance activities. The information system currently provided by UNS is not yet able to complete PSTI's needs for monitoring and quality assurance functions at the study program level. A solution that has been proven to be able to solve similar problems is through the use of an information dashboard or dashboard. The unavailability of dashboards and PSTI's urgent need for study program performance monitoring activities led this research to design a dashboard in accordance with PSTI's needs and ensure that the design developed could be used immediately. To ensure the success of the design, this research uses a user-centric method in the design process and heuristic usability testing as an evaluation stage. This research produced a dashboard design, data filling template, and a guidebook that was used to make dashboard use easier. The successfully designed dashboard has more complete study program level information from the information system provided by UNS and has succeeded in meeting the needs of PSTI users with a user satisfaction level of 7.6. Based on the level of implementation readiness, this dashboard scored 86.83% for its usability test with minor problems. The root of the problem identified has been found and repaired.